A novel fatigue-oxidation-creep life prediction method under non-proportional loading. (January 2022) - Li, Dao-Hang; Shang, De-Guang; Yin, Xiang; Li, Ming; Chen, Feng; Sun, Guo-Qin; Sun, Wei
Highlights: Multiaxial fatigue behavior at high temperature is experimentally characterized. Fatigue-oxidation-creep damage behaviors are comprehensively captured. The effect of non-proportional hardening on fatigue behavior is considered. The notch stress–strain history is determined by the elastic-viscous-plastic analysis. A new method is proposed to evaluate the fatigue life and applied to a notched bar. Abstract: In this paper, a new life assessment framework is proposed based on the elastic-viscoplastic modeling and the damage behavior for the structural component under multiaxial non-proportional loading at high temperature. The viscoplastic constitutive model with the ability to capture the non-proportional hardening effect is used to obtain the stress–strain fields, in which a new method based on the rotation of strain axis is proposed to evaluate the notch rotation factor. The damage model, which can comprehensively capture the multiaxial fatigue-oxidation-creep behaviors, is used to assess the failure life. In addition, the proposed framework is evaluated by the life results under proportional and non-proportional fatigue loadings at 650 °C, and the errors are found to be within a factor of 2.